GABAergic System Dysfunction and Challenges in Schizophrenia Research - Jahangir, Muhammad; Zhou, Jian-Song; Lang, Bing; Wang, Xiao-Ping (Frontiers in Cell and Developmental Biology, 2021)
Despite strenuous study since last century, the precise cause and pathology of schizophrenia are still largely unclear and arguably controversial. Although many hypotheses have been proposed to explain the etiology of schizophrenia, the definitive genes or core pathological mechanism remains absent. Among these hypotheses, however, GABAergic dysfunctioning stands out as a common feature consistently reported in schizophrenia, albeit a satisfactory mechanism which could be exploited for therapeutic purpose has not been developed yet. This review is focusing on the progress made to date in the field in terms of understanding the mechanisms involving dysfunctional GABAergic system and loops identified in schizophrenia research.